2015
DOI: 10.2174/1567201812666150901112544
|View full text |Cite
|
Sign up to set email alerts
|

Nanoemulsion-based Parenteral Drug Delivery System of Carbamazepine: Preparation, Characterization, Stability Evaluation and Blood-Brain Pharmacokinetics

Abstract: Carbamzepine (CBZ) was encapsulated in a parenteral oil-in-water nanoemulsion, in an attempt to improve its bioavailability. The particle size, polydispersity index and zeta potential were measured using dynamic light scattering. Other parameters such as pH, osmolality, viscosity, drug loading efficiency and entrapment efficiency were also recorded. Transmission electron microscopy revealed that emulsion droplets were almost spherical in shape and in the nano-range. The in vitro release profile was best charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…It is important to note that CBZ release was extremely low (<2%) in the coarse emulsions as well as nanoemulsions at very early time points. The CBZ release was lower than anticipated based on the results of previous publications examining emulsified CBZ systems [47][48][49][50][51]. However, the previous studies examined CBZ release under different conditions: (i) CBZ in lower amounts, (ii) different types of oil phase, (iii) higher concentrations of surfactants, and (iv) use of dialysis membranes with large cutoff sizes.…”
Section: Analytical Methodology For Drug Quantificationmentioning
confidence: 68%
“…It is important to note that CBZ release was extremely low (<2%) in the coarse emulsions as well as nanoemulsions at very early time points. The CBZ release was lower than anticipated based on the results of previous publications examining emulsified CBZ systems [47][48][49][50][51]. However, the previous studies examined CBZ release under different conditions: (i) CBZ in lower amounts, (ii) different types of oil phase, (iii) higher concentrations of surfactants, and (iv) use of dialysis membranes with large cutoff sizes.…”
Section: Analytical Methodology For Drug Quantificationmentioning
confidence: 68%
“…There are abundant merits for nanoemulsion-based delivery systems over other dosage forms, such as high surface area, unique transparent appearance, tunable rheology, good stability and bioavailability, and rapid and efficient penetration of the drug moiety [111-118]. Nanoemulsion is currently employed as an important drug carrier in the development of drug formulations for providing pharmaceutically accepted ingredients [112, 119-121].…”
Section: Integration Of Drug Carriers In Microfluidic Platformsmentioning
confidence: 99%
“…The polysorbate 80 based nanoemulsion increased the brain bioavailability up to 7.4 folds than the other formulations. 104 Similarly, Tan et al (2015) also used parenteral nanoemulsion for brain targeting of carbamazepine to treat seizure and evaluated its pharmacokinetic efficiency. The study shows higher pharmacokinetic profile and lower side effects of the drug when delivered as nanoemulsion than the free drug solution which assures the potency of carrier system.…”
Section: Nanoemulsionmentioning
confidence: 99%
“…The study shows higher pharmacokinetic profile and lower side effects of the drug when delivered as nanoemulsion than the free drug solution which assures the potency of carrier system. 105 From the available research work, it can be concluded that mucoadhesive nanoemulsion mostly intended for parenteral and intranasal administration to the brain was extensively studied and found as promising carrier system which reduces the associated adverse effect, improves the therapeutic potency and offers a non-invasive patient-friendly technique to access the brain. 106…”
Section: Nanoemulsionmentioning
confidence: 99%